Estado de salud bucal de niños con diagnóstico de VIH-Sida en la fundación Eudes de Medellín. Presentación de casos y revisión de literatura (2004)
ABSTRACT: HIV-AIDS is an infectious contagious disease which compromises the immune system with multiple manifestations, some of them in the oral cavity. The purpose of this article is to review recent literature and describe the oral health status of 9 children with HIV-AIDS under ten years of age, who are presently living at the EUDES Foundation in Medellin. The dental caries history, the level of oral hygiene, the soft tissue lesions as well as the type and frequency of medication used and its relationship to clinical findings was established. The information was obtained by means of an intra oral examination and the clinical history. A deficient oral hygiene (evaluated with the Sillness and Loe Index) was found and a very low index of dental caries and gingival disease. Ulcers of idiopathic origin were found in the soft tissues, as well a greenish hairy tongue with atrophy of papillae. Pigmentations in the mucosa and localized gingivitis were prevalent. The majority of the lesions found seem to be originated as secondary effects of the medications and not as lesions associated to the systemic condition of the patient.